(untitled) (Texas Journal of Medical Science, 2026)
Nasal breathing disorders are increasingly recognized as serious health concerns in the pediatric population. Recent research points to a robust connection between compromised nasal airflow and a variety of cognitive deficits in children. Persistent mouth breathing associated with nasal obstruction often results in altered craniofacial development and impacts sleep quality, which in turn can disrupt optimal brain maturation and neurocognitive functioning. This paper discusses the importance of monitoring cognitive functions in children affected by nasal breathing disorders, the neurobiological mechanisms linking respiratory impairment and cognitive deficits, available assessment methods, and evidence-based interventions. Special attention is given to the challenges in early detection, the role of multidisciplinary collaboration, and the implications for long-term developmental and academic outcomes.